2022
DOI: 10.34172/apb.2023.047
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Targets for Cancer Diagnosis: Interests and Limitations

Abstract: MicroRNAs are small RNAs with ability to attach to the large number of RNA that regulate gene expression on postranscriptional level via inhibition or degradation of specific mRNAs. MiRNAs in cells are the primary regulators of functions such as cell growth, differentiation, and apoptosis and considerably influence cell function. The expression levels of microRNAs change in human diseases, including cancer. These changes highlight their essential role in cancer pathogenesis. Ubiquitous irregular expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Several miRNAs act as either tumor suppressors or oncogenes by targeting genes associated with cancer. Between 30% and 80% of protein-coding genes have at least one binding site for miRNA, giving miRNAs the ability to control the expression of multiple mRNAs by partially binding to them ( 22 ). MiRNAs are critical for the regulation of gene expression because they specifically target mRNA and implement various post-transcriptional mechanisms, such as translation inhibition and mRNA degradation ( 23 ).…”
Section: Alterations Of Mirna In Breast Cancermentioning
confidence: 99%
“…Several miRNAs act as either tumor suppressors or oncogenes by targeting genes associated with cancer. Between 30% and 80% of protein-coding genes have at least one binding site for miRNA, giving miRNAs the ability to control the expression of multiple mRNAs by partially binding to them ( 22 ). MiRNAs are critical for the regulation of gene expression because they specifically target mRNA and implement various post-transcriptional mechanisms, such as translation inhibition and mRNA degradation ( 23 ).…”
Section: Alterations Of Mirna In Breast Cancermentioning
confidence: 99%
“…In addition, studies have shown that a single mRNA can be regulated by multiple miRNAs. 9,10 These processes include metabolism, neurodevelopment, neuroplasticity, and apoptosis, which are fundamental to the functioning of the nervous system. 11 Several studies have shown the correlation between miR-125b and mir-107 expression changes and oxidative stress.…”
mentioning
confidence: 99%
“…Dysregulated miRNAs in cancers can serve as diagnostic and prognostic biomarkers [ 2 , 3 ]. Extensive profiling of microRNA (miRNA) expression patterns in tumorous and adjacent non-tumor tissues has yielded abundant miRNA signatures with potential prognostic and therapeutic implications [ 4 ].…”
mentioning
confidence: 99%